Foreign Aids and Poverty in Nigeria: An Examination of the Nexus - Muru Bitrus Song; Ogungbotemi, O. S (Penerbit Hellow Pustaka, 2025)
Poverty is a major challenge in Nigeria as a developing country, hence this study investigated the impact of foreign aid on poverty reduction in Nigeria for the period 1981-2023. The study used Augmented Dickey-Fuller (ADF), Granger causality technique and Auto Regressive Distributed Lag (ARDL). The ADF showed that poverty index, Official Development Assistance (ODA) and population were greater than their respective critical values; hence, suggest that poverty index and Official Development Assistance (ODA) were not integrated of order zero but of order one; while, foreign direct investment and inflation were integrated of order zero. Also, the bound test confirmed co-integration between the variables, which means that there is a long-run relationship between the variables. The granger causality confirmed a unidirectional causality between foreign aid poverty in Nigeria, implying that the change in the country's poverty levels are a result of foreign aid. Furthermore, the ARDL estimate showed that foreign aid reduces poverty in Nigeria in the short-run and long-run, with a higher level of reduction in the long-run, while population increases poverty in Nigeria in the short-run and long-run, with a higher level of increase in the long-run. This suggests that foreign aid helps to reduce poverty in the country, and sustained overtime. The study concluded that while foreign aid reduced poverty, population tend to aggravate the challenge of poverty. Therefore, recommended that since ODA led to a decrease in poverty level, the government should utilise ODA more effectively to reduce poverty in Nigeria. This requires securing more ODA and identifying the sectors of the economy that should be prioritized when ODA is to be used.